Enterprise and economic development in Africa - Nziku, Dina M.; Struthers, J. J. (Emerald Group Publishing, 2021)
Presenting a topical analysis of the challenges and achievements of enterprise, Enterprise and Economic Development in Africaexamines contributions to economic development on the continent, as well as exploring implications for policy dimensions.